Peran Guru dalam Proses Difusi Inovasi Pendidikan : Studi tentang Pengaruh Pelatihan dan Pengembangan Profesional - Evi Tri Prihatini; Meri Meri; Yohanes Bahari; Waneri Waneri (Journal on Education, 2024)
Innovation in education plays an important role in improving the quality of learning and professionalism of teaching staff. This research focuses on the role of teachers as agents of change in the diffusion of educational innovations, especially in adopting new learning technologies and pedagogical approaches. This study uses a qualitative method with a literature study approach, which includes analysis of literature from books, journals and research reports. Research findings show that teacher readiness and support, such as training and ongoing professional development, greatly influence the success of innovation adoption. Inhibiting factors such as resistance to change and limited resources are also found to be obstacles in the diffusion of innovation. Therefore, institutional support and educational policies that strengthen teacher capacity are very necessary to accelerate the adoption process and improve the overall quality of education.